The structure of sexual networks determines the operation of sexual selection - McDonald, G; Pizzari, T (National Academy of Sciences, 2018)
Sexual selection is a fundamental evolutionary process, but remains debated particularly in the complexity of polyandrous populations where females mate with multiple males. This lack of resolution is partly because studies have largely ignored the structure of the sexual network, i.e. the pattern of mate sharing. Here, we quantify what we call mating assortment with network analysis to specify explicitly the indirect as well as direct relationships between partners. We first review empirical studies, showing that mating assortment varies considerably in nature, due largely to basic properties of the sexual network (size and density), and partly to non-random patterns of mate sharing. We then use simulations to show how variation in mating assortment interacts with population-level polyandry to determine the strength of sexual selection on males. Controlling for average polyandry, positive mating assortment, arising when more polygynous males tend to mate with more polyandrous females, drastically decreases the intensity of precopulatory sexual selection on male mating success (Bateman gradient) and the covariance between male mating success and postcopulatory paternity share. Average polyandry independently weakened some measures of sexual selection, and crucially also impacted sexual selection indirectly by constraining mating assortment through the saturation of the mating network. Mating assortment therefore represents a key -albeit overlooked- modulator of the strength of sexual selection. Our results show that jointly considering sexual network structure and average polyandry more precisely describes the strength of sexual selection.